Health Information Literacy and Barriers of Online Health Information Seeking Among Digital Immigrants in Rural China: A Preliminary Survey. (June 2019) - Fuzhi, Wang; Dan, Luo; Weiwei, Sun; Tingting, Yan; Dehua, Hu; Wei, Pan; Aijing, Luo
To evaluate the health information literacy (HIL) level and influencing factors among digital immigrants in rural China and to investigate their obstacles of online health information seeking. Cross-sectional study. Digital immigrants aged 45 to 65 in rural China. Self-assessment questionnaires and a semi-structured interview were developed to measure HIL among 1, 132 participants. Nonparametric tests and multiple linear regression were employed to explain the influencing factors. The HIL level of digital immigrants is low. Age, education level, and experience of Internet use impacted their HIL. Digital immigrants primarily accessed the Internet via mobile terminals, but their poor information skills, their lack of HIL education, and the low readability of online health information are major barriers of online health information seeking. Although respondents recognized the positive effects of health-related information on health promotion, their abilities to seek, evaluate, and apply health information were weak. The government should incorporate HIL into the national health literacy promotion program and strengthen legislative supervision of online health information.